Chitosan oligosaccharide improves ovarian granulosa cells inflammation and oxidative stress in patients with polycystic ovary syndrome - Xie, Qi; Hong, Wenli; Li, Yuan; Ling, Shuyi; Zhou, Ziqiong; Dai, Yuqing; Wu, Wenbo; Weng, Ruoxin; Zhong, Zhisheng; Tan, Jun; Zheng, Yuehui (Frontiers in Immunology, 2023)
Polycystic Ovary Syndrome is the most common reproductive endocrine disorder among women of reproductive age, which is one of the main causes of anovulatory infertility. Even though the rapidly developed assisted reproductive technology could effectively solve fertility problems, some PCOS patients still have not obtained satisfactory clinical outcomes. The poor quality of oocytes caused by the abnormal follicular development of PCOS may directly contribute to the failure of ART treatment. Ovarian granulosa cells are the most closely related cells to oocytes, and changes in their functional status have a direct impact on oocyte formation. Previous studies have shown that changes in the ovarian microenvironment, like oxidative stress and inflammation, may cause PCOS-related aberrant follicular development by impairing the physiological state of the GCs. Therefore, optimizing the ovarian microenvironment is a feasible method for enhancing the development potential of PCOS oocytes. In this study, we first detected the expression of inflammatory-related factors (TGF-β1, IL-10, TNFα, IL-6) and oxidative stress-related factors (HIF-1α and VEGFA), as well as the proliferation ability and apoptosis level of GCs, which were collected from control patients (non-PCOS) and PCOS patients, respectively. Subsequently, human ovarian granulosa cell line (KGN) cells were used to verify the anti-inflammatory and anti-oxidative stress effects of chitosan oligosaccharide (COS) on GCs, as well as to investigate the optimal culture time and concentration of COS. The optimal culture conditions were then used to culture GCs from PCOS patients and control patients. The results showed that GCs from PCOS patients exhibited obvious inflammation and oxidative stress and significantly reduced proliferation and increased apoptosis. Furthermore, COS can increase the expression of anti-inflammatory factors (TGF-β1 and IL-10) and decrease the expression of pro-inflammatory factors (TNFα and IL-6), as well as promote the proliferation of GCs. Moreover, we found that COS can reduce the level of reactive oxygen species in GCs under oxidative stress by inhibiting the expression of HIF-1α and VEGFA and by suppressing the apoptosis of GCs induced by oxidative stress. In conclusion, inflammation and oxidative stress exist in the GCs of PCOS patients, and COS can reduce these factors, thereby improving the function of GCs.